FREQUENCY OF HYPOTHYROIDISM AMONG HYPONATREMIC PATIENTS - Dr Muhammad Ayaz Khan; Dr Hafiza Amna Benazir; Dr Amna Khalid; Dr Niaz Ahmed; Dr Dial Das; Dr Momin Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Hyponatremia is a fairly common electrolyte disorder which is frequently associated with endocrine conditions such as hypothyroidism but whose direct causal relationship is far from clear. They are relevant because their association must be understood for effective diagnosis and management. Objective: The aim of the study was to determine the frequency of hypothyroidism among hyponatremic patients in a hospital in Pakistan. Materials and Method: The study done at Aga Khan University Hospital Karachi from February, 2024 to July, 2024 is a descriptive cross-sectional one. Those with known hyponatremia causes were excluded, and patients with serum sodium <135 mmol. Hypothyroidism was assessed by thyroid function tests, and the data were described through descriptive statistics. Results: Of 150 hyponatremic patients (58.7% male, mean age 52.4 years), 22.7% had hypothyroidism (16.7% overt, 6.0% subclinical). Hypothyroid patients were older (mean age 58.3 years) and more likely female (27.4%). Euvolemic hyponatremia was predominant (70.6%) in hypothyroid patients, with a significant association (p < 0.05). Conclusion: Hypothyroidism is a notable contributor to hyponatremia, particularly in older females. Routine thyroid screening is recommended for hyponatremic patients to ensure timely diagnosis and treatment.